Evaluación del sistema hidráulico de agua potable de Alimentos Prosalud - Salas-Villalobos, Esteban (Instituto Tecnológico de Costa Rica, 2014)
With the passage of time Alimentos Prosalud has made variations in their production processes, new equipment has been installed and there have been movements at the location of the existing equipment. The installation and movement of equipment have been made without documentation and without considering that, changes in the distribution of potable water, can cause changes in the regime of operation of the pumping system. To document the installation and changes in the position of equipment, new drawings of the distribution of drinking water were made. In order to assess the impact of changes in the potable water, the sizing of branch of water distribution of sardine production process was evaluated, according to the recommendations given by ASHRAE and CIHSECR. There are thirty flowmeters installed in the potable water distribution network, one of them corresponds to the general flow meter and record the total water consumption of the company. The sum of the consumption recorded by the others flowmeters is lower by 40% compared to the data recorded by the main flowmeter, this evidence, that records of water usage by department and cost distribution in accordance with established business units, are not reliable. In order to evaluate the performance of flowmeters, a check is made using an ultrasonic flow meter, and the network installation conditions and configuration of flowmeters are reviewed. Tests were performed in the flowmeter calibration laboratory of Elvatron company, to determine the accuracy of an ultrasonic flowmeter, and a vortex flowmeter type, in different installation and flow conditions.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2014.
Keywords: Diseño de proyectos; Caudales; Tuberías; Medidas de caudal; Producción; Técnica de producción